Anthropometric and functional characteristics of athletes involved in combat sports in the Greco-Roman style - E. V. Kharlamov (Спортивная медицина: наука и практика, 2020)
Objective: to determine the morphological and functional parameters of athletes-junior wrestlers, determining their specialization, qualification and training in ontogenesis. Materials and methods: 49 male junior athletes of the school of Olympic reserve engaged in martial arts in the GrecoRoman style for 6-10 years were examined. We used the Dorokhov R.N. (1994) technique of selection and early orientation in sports to determine the anthropometric temporal characteristics. Following functional indicators were determined: absolute and relative physical performance, aerobic performance, power index eagerly, type of vegetative regulation. Results: the majority of fighters teenagers CMS had mesosomal, microcorpulent, micromesomelic, micromesic and mesomacromembral somatotype. A comprehensive study of the functional parameters of the wrestlers showed that indicators of absolute and relative physical performance were higher in young men CMS and were respectively 1318.6±149.5 kg∙m/min and 19.3±2.5 kg∙m/(min∙kg). Aerobic performance was higher in adolescents and first-rank sportsmen: 51.8±9.36 ml/(min∙kg). The strength indices of the hands were higher in the young men's CMS and contributed to 70.6±6.37% for the right hand and 66.08±12.1% for the left hand, which was explained by the component body composition of the body of young men. Most of the wrestlers revealed moderate parasympathicotonia and amphotonic. Conclusions: the R.N. Dorokhova and V.G. Petrukhina (1994) method of somatotyping allows to differentiate athletes, involved in martial arts in the Greco-Roman style, into 3 levels of variation: dimensional, component and proportion and to determine their specialization, qualification and degree of training in ontogenesis.